Effect of L-carnitine and paylean (ractopamine⋅HCl) supplementation on growth performance, carcass characteristics, and postmortem pH decline - James, B.W.; Owen, K.Q.; Lawrence, T.E.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Unruh, John A.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Growth performance, carcass characteristics, and meat quality were evaluated from 126 pigs fed combinations of Paylean and L-carnitine arranged in a 2 × 3 factorial. Dietary L-carnitine (0, 25, or 50 ppm) and Paylean (0 or 9 g/ton) were fed the last 4 weeks prior to slaughter. Feeding Paylean to pigs improved (P<0.01) ADG and F/G. Supplemental Lcarnitine did not affect (P>0.46) ADG, but there was a trend for improved (quadratic, P<0.07) F/G in pigs fed increasing carnitine. A carnitine × Paylean interaction (P<0.05) was observed for dressing percentage and visual firmness, percentage transmission (soluble protein), temperature measured 1.5 h postmortem, and percentage drip loss. Dressing percentage was higher for pigs fed 25 ppm carnitine with no Paylean and lower for pigs fed 25 ppm carnitine with Paylean. Visual firmness scores decreased in pigs fed increasing carnitine and no Paylean but increased when adding carnitine to diets containing Paylean. Soluble protein increased (more soluble protein indicates higher quality muscle) and drip loss decreased when pigs were fed increasing L-carnitine with Paylean. A trend (P<0.07) was observed for pigs fed increasing carnitine to have lower 10th rib and average backfat. Feeding Paylean to pigs increased (P<0.01) percentage lean, L*, and hue angle, and decreased (P<0.02) visual color scores and a*/b* values. Pigs fed Paylean had higher temperature and lower pH measured 3 h postmortem (P<0.01) and tended (P<0.06) to have lower pH measured 6 h postmortem. These results suggest that Paylean improves growth performance when fed to finishing pigs. Carnitine decreased drip loss and improved meat quality when fed to pigs in combination with Paylean.
Keywords: Carnitine; Paylean; Meat Quality; Swine